2022
DOI: 10.2147/jbm.s360091
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Wateen App in the Blood-Donation Process in Saudi Arabia

Abstract: Background Blood transfusions are essential for many medical procedures, but current supplies of blood are insufficient to meet the needs of all patients. Apps offer a means to improve donor recruitment and enhance blood-donation systems, if they are usable and useful. The Saudi Ministry of Health launched a blood-donation app, “Wateen”. However, there is currently no evidence of the app’s usability and usefulness among users. Purpose The aim of this research was to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Participants felt that the App increases awareness and understanding by providing information, that it facilitates better communication between donation centers and donors, and that it increases efficiency by making it simpler to recruit donors and by pointing them in the direction of the donation centers that are most convenient for them. The benefits mentioned here are consistent with those found in earlier studies [13].…”
Section: Findings Summarysupporting
confidence: 93%
“…Participants felt that the App increases awareness and understanding by providing information, that it facilitates better communication between donation centers and donors, and that it increases efficiency by making it simpler to recruit donors and by pointing them in the direction of the donation centers that are most convenient for them. The benefits mentioned here are consistent with those found in earlier studies [13].…”
Section: Findings Summarysupporting
confidence: 93%
“…The research conducted by Tsai et al (45) found that the main factors influencing the adoption of social media among older adults were user interface design, navigation, and system support, as determined through a quantitative questionnaire taken from 101 older adults over 50 years of age. This view was also supported by Castilla et al (85), Alessa (86), and Gao et al (87). In order to overcome the problem of older adults' unwillingness to use new technologies such as mobile…”
Section: User Interface Quality Influencing Factorsmentioning
confidence: 74%